Preparation method and application of hydrogen production particles with porous structures

By combining metal hydrides and structural stabilizers in the molten particles, the pore structure is optimized, and the problem of insufficient efficiency of existing hydrogen storage technology is solved, and efficient hydrogen storage and release is achieved, with wide application prospects.

CN119503725APending Publication Date: 2025-02-25YANCHENG TEACHERS UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411707059.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing hydrogen storage technology has shortcomings in terms of safety, cost and energy efficiency, and the hydrogen storage efficiency and hydrogen release rate of porous materials in the field of hydrogen storage still need to be improved.

Method used

Hydrogen production particles with porous structures are used to optimize pore structure and chemical properties by combining metal hydrides and structural stabilizers (such as carbon nanotubes or metal oxides), and improve the adsorption/desorption efficiency of hydrogen.

Benefits of technology

It significantly improves the hydrogen storage and release efficiency and stability of hydrogen, improves the hydrogen production catalytic and hydrogen storage performance, and has a wide range of application prospects in the storage and utilization of hydrogen energy, green chemistry and sustainable industrial processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503725A_ABST
    Figure CN119503725A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of hydrogen production particles with a porous structure, belongs to the technical field of hydrogen production, and improves the efficiency and stability of hydrogen storage and hydrogen release through the combination of a specific metal hydride and a structural stabilizer. Through a specific preparation method, such as ball milling and thermal annealing processes, the uniformity and structural integrity of the particles are ensured, and meanwhile, a special pore forming agent is introduced for preparation, so that the porosity of the hydrogen production particles is further remarkably improved, and the hydrogen production catalysis and hydrogen storage performance of the hydrogen production particles are improved. In addition, the particles have a wide application prospect as a catalyst carrier in a chemical reaction or in a hydrogen storage system, and especially show unique performance in improving the efficiency of a hydrogenolysis reaction of organic compounds and controlling the adsorption and release process of hydrogen in the hydrogen storage system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen production, and more specifically to a method for preparing hydrogen production particles with a porous structure and application thereof. Background Art

[0002] As a clean energy, hydrogen has the advantages of high energy density and does not produce greenhouse gases when burned or used. This makes hydrogen a key component in achieving a sustainable energy system. However, the effective storage and transportation of hydrogen is one of the main technical challenges in achieving its widespread application. Since hydrogen is a low-density gas at room temperature and pressure, it usually needs to be compressed or liquefied under high pressure for storage, which not only increases energy consumption but also brings safety risks.

[0003] Current hydrogen storage technologies mainly include high-pressure gas storage, liquid hydrogen storage and solid-state storage. Although high-pressure gas storage and liquid hydrogen storage are mature technologies, they are insufficient in terms of safety, cost and energy efficiency. Solid-state storage, especially the method using metal hydrides, provides a safer storage method, but its hydrogen release rate and the high reaction temperature required limit its application range.

[0004] In order to solve the limitations of traditional hydrogen storage technology, researchers have developed hydrogen storage technology based on porous materials. Porous materials can adsorb more hydrogen at lower pressures and temperatures due to their high specific surface area and adjustable pore structure. These materials include activated carbon, metal-organic frameworks (MOFs), and porous polymers.

[0005] Although porous materials have shown potential in the field of hydrogen storage, how to further improve their hydrogen storage efficiency and hydrogen release rate remains a key scientific research issue. The porous structure hydrogen production particles proposed in this invention combine metal hydrides and structural stabilizers (such as carbon nanotubes or metal oxides) to optimize the pore structure and chemical properties of these materials, thereby improving the adsorption / desorption efficiency of hydrogen and its activity at lower temperatures.

[0006] In addition, the porous structure hydrogen production particles can not only be used for efficient hydrogen storage, but also as catalyst carriers for catalyzing the hydrogenolysis reaction of organic compounds. The development of such particles is expected to find wide applications in the storage and utilization of hydrogen energy, green chemistry, and sustainable industrial processes. Summary of the invention

[0007] 1. Technical issues to be solved

[0008] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing hydrogen-producing particles with a porous structure and its application, which improves the efficiency and stability of hydrogen storage and hydrogen release through a combination of specific metal hydrides and structural stabilizers. Through specific preparation methods, such as ball milling and thermal annealing processes, the uniformity and structural integrity of the particles are ensured, and at the same time, special pore formers are introduced for preparation, which further significantly improves the porosity of the hydrogen-producing particles and enhances their hydrogen production catalysis and hydrogen storage performance. In addition, these particles have broad application prospects as catalyst carriers in chemical reactions or in hydrogen storage systems, especially in improving the efficiency of hydrogenolysis reactions of organic compounds and controlling the adsorption and release of hydrogen in hydrogen storage systems. They show unique performance.

[0009] 2. Technical solution

[0010] To solve the above problems, the present invention adopts the following technical solutions.

[0011] A porous hydrogen-producing particle, the particle consists of a metal hydride and a structural stabilizer, wherein the metal hydride is selected from at least one of magnesium hydride (MgH2), nickel hydride (NiH2) and iron hydride (FeH2), and the structural stabilizer is a carbon nanotube or a metal oxide.

[0012] As a further improvement of the present invention, the mass ratio of the metal hydride is 50-90%, and the mass ratio of the structural stabilizer is 10-50%.

[0013] As a further improvement of the present invention, it further comprises a pore former, wherein the pore former accounts for 1-5% of the mass of the particles.

[0014] A method for preparing hydrogen-producing particles with a porous structure comprises the following steps:

[0015] a. Mixing metal hydride and structural stabilizer in a certain proportion;

[0016] b. The mixture is subjected to ball milling at room temperature to form a uniformly mixed powder;

[0017] c. Pressing the ball-milled powder into particles and curing them by natural curing or thermal annealing, wherein the heating temperature of the thermal annealing is not higher than 200°C.

[0018] As a further improvement of the present invention, in step c, after the particles are solidified, the surfaces are chemically modified to introduce amino or carboxyl functional groups, thereby providing additional adsorption sites or improving the interaction between the particles and hydrogen, including the following processing steps:

[0019] C1. Clean the particles in an ultrasonic cleaner using a solvent such as ethanol or acetone, and then dry them in an oven;

[0020] C2. For the introduction of amino functional groups, aminopropyltriethoxysilane (APTES) can be selected as a modifier, and for the introduction of carboxyl functional groups, carboxypropyltriethoxysilane (CPTES) can be selected as a modifier;

[0021] C3, soaking the prepared particles in a solution containing a modifier and reacting at room temperature for 1-2 hours;

[0022] C4, recovering the modified particles from the reaction mixture and washing them thoroughly with ethanol to remove unreacted modifiers and byproducts;

[0023] C5. Finally, the cleaned particles are dried at 30-40°C for 1-5 hours to ensure that the modifier is solidified and stably attached to the particle surface.

[0024] As a further improvement of the present invention, the specific steps of adding the pore forming agent are as follows:

[0025] S1. Prepare a pore former of corresponding mass, and evenly mix 80-90% of the mixed powder and 60-80% of the pore former after step b;

[0026] S2, pressing and molding the mixed product of step S1 to form initial particles, and uniformly mixing the remaining mixed powder with the pore-forming agent to wrap the initial particles for secondary pressing and molding to form final particles;

[0027] S3. The final particles are treated to eliminate the pores left by the pore former to form hydrogen-producing particles.

[0028] As a further improvement of the present invention, after step S3, the metal organic framework material ZIF-8MOF is filled into the porous structure of the hydrogen production particles, and the specific filling steps are as follows:

[0029] S4. Preparation of MOF precursor: Dissolve zinc acetate in DMSO, the mass ratio of zinc acetate to DMSO is (0.8-1):10, slowly add 2-methylimidazole, and continue stirring until completely dissolved, the mass ratio of 2-methylimidazole to DMSO is (1-1.2):10;

[0030] S5. Impregnation: Immerse the hydrogen-producing particles in the above solution and keep them still for 12 to 24 hours to ensure that the precursor fully penetrates the interior of the particles;

[0031] S6. Low temperature heat treatment: placing the impregnated particles in an oven preheated to 100°C for 2-3 hours to promote ZIF-8 crystallization;

[0032] S7, cooling and recycling: taking out the treated particles from the oven, cooling them naturally to room temperature, washing the particles with pure DMSO to remove unreacted precursors and impurities, and then drying them at 60-80°C for 1-2 hours.

[0033] As a further improvement of the present invention, the pore former is one of gelatin and carboxymethyl cellulose, and step S3 is eliminated by a corresponding low-temperature treatment method.

[0034] The invention discloses an application of hydrogen-producing particles with a porous structure. The particles are used as catalyst carriers to catalyze hydrogenolysis reactions of organic compounds.

[0035] As a further improvement of the present invention, the particles are also used in a hydrogen storage system, wherein the porous structure increases the adsorption and release efficiency of hydrogen.

[0036] 3. Beneficial effects

[0037] The present invention improves the efficiency and stability of hydrogen storage and hydrogen release through a combination of specific metal hydrides and structural stabilizers. Through specific preparation methods, such as ball milling and thermal annealing processes, the uniformity and structural integrity of the particles are ensured, and at the same time, a special pore former is introduced for preparation, which further significantly improves the porosity of the hydrogen-producing particles and enhances their hydrogen production catalysis and hydrogen storage performance. In addition, these particles have broad application prospects as catalyst carriers in chemical reactions or in hydrogen storage systems, especially in improving the efficiency of organic compound hydrogenolysis reactions and controlling the adsorption and release of hydrogen in hydrogen storage systems. Unique performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a flow chart of the preparation of hydrogen production particles of the present invention;

[0039] Figure 2 This is a comparison table of catalyst performances of Examples 7-13 of the present invention;

[0040] Figure 3 This is a table of test results of the hydrogen storage system of Examples 14-17 of the present invention;

[0041] Figure 4 Impact analysis table of pore formers in Examples 4-7 of the present invention. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments, and all other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making creative work are within the scope of protection of the present invention.

[0043] Embodiment 1:

[0044] Magnesium hydride (MgH2) was used as the main metal hydride and carbon nanotubes were used as structural stabilizers. First, magnesium hydride was taken at a mass ratio of 70% and carbon nanotubes were taken at a mass ratio of 30%. After the two materials were mixed, they were ball milled at room temperature for 6 hours to ensure sufficient mixing. Subsequently, the mixture was pressed under a pressure of 300 MPa to form particles. Finally, the particles were thermally annealed in a nitrogen atmosphere at a temperature of 180°C for 2 hours to solidify the particle structure.

[0045] Embodiment 2:

[0046] Magnesium hydride (MgH2) was used as the main metal hydride and carbon nanotubes were used as structural stabilizers. First, 80% of magnesium hydride and 20% of carbon nanotubes were taken by mass. After the two materials were mixed, they were ball milled at room temperature for 6 hours to ensure sufficient mixing. Subsequently, the mixture was pressed under a pressure of 400 MPa to form particles. Finally, the particles were thermally annealed at 180°C in a nitrogen atmosphere for 2 hours to solidify the particle structure.

[0047] Embodiment 3:

[0048] Nickel hydride (NiH2) was selected as the metal hydride and zinc oxide (ZnO) as the structural stabilizer. The mixture was mixed at a mass ratio of 60% lithium aluminum hydride and 40% zinc oxide. The mixture was ball milled at room temperature, then pressed under a pressure of 150 MPa and thermally annealed at 180°C for 2 hours to solidify the particle structure.

[0049] Embodiment 4:

[0050] Magnesium hydride (MgH2) is used as the main metal hydride and carbon nanotubes are used as structural stabilizers. First, magnesium hydride is taken at a mass ratio of 70% and carbon nanotubes are taken at a mass ratio of 30%. After the two materials are mixed, they are ball milled at room temperature for 6 hours to ensure sufficient mixing. Subsequently, a pore former with a mass ratio of 2% is mixed again, pressed under a pressure of 300MPa, and then the final particles are treated to eliminate the pores left by the pore former to form hydrogen-producing particles. Finally, the particles are thermally annealed in a nitrogen atmosphere at a temperature of 180°C for 2 hours to solidify the particle structure.

[0051] The pore former is a material that can be decomposed at low temperature and does not chemically react with the metal hydride or the structure stabilizer. Step S3 uses a corresponding low-temperature treatment method to eliminate it.

[0052] The pore former is one of gelatin and carboxymethyl cellulose.

[0053] CMC is a soluble cellulose derivative that can be decomposed under appropriate conditions. It can be removed by water washing or dissolution at low temperatures.

[0054] Gelatin is a soluble protein that can be decomposed under appropriate conditions. It can be removed by water washing or enzymatic hydrolysis.

[0055] These materials can be directly decomposed even when heated to below 100 degrees Celsius, without the need for further processing steps.

[0056] In this embodiment, gelatin powder of suitable size is preferred, usually ranging from 1 micron to 500 microns. The pressed material is placed in a furnace and heated to 60°C for a sufficient time to ensure that the gelatin powder is completely decomposed and evaporated.

[0057] In this embodiment, this method can accurately control the size and distribution of pores. By controlling the amount of pore former and the particle size, the size and distribution of pores in the prepared hydrogen-producing particles can be determined to a certain extent, including the improvement of porosity, which can be controlled in the process.

[0058] Compared with Examples 1-3, the porosity of the hydrogen-producing particles prepared in Example 4 is significantly improved, and the subsequent catalytic hydrogen production effect and hydrogen storage effect are also significantly improved.

[0059] Embodiment 5:

[0060] Magnesium hydride (MgH2) is used as the main metal hydride and carbon nanotubes are used as structural stabilizers. First, magnesium hydride is taken in a mass ratio of 70% and carbon nanotubes are taken in a mass ratio of 30%. After the two materials are mixed, ball milling is performed at room temperature for 6 hours to ensure sufficient mixing. Subsequently, a pore former with a mass ratio of 2% is taken for standby use, 80-90% of the mixed powder is taken and 60-80% of the pore former is uniformly mixed, the mixed product is pressed to form initial particles, the remaining mixed powder is uniformly mixed with the pore former and then the initial particles are wrapped for secondary pressing to form final particles, which are pressed under a pressure of 300MPa, and then the final particles are treated to eliminate the pores left by the pore former to form hydrogen-producing particles, and finally, the particles are thermally annealed in a nitrogen atmosphere at a temperature of 180°C for 2 hours to solidify the particle structure.

[0061] Compared with Example 4, Example 5 has an improved surface porosity and a slightly improved overall porosity. This is because the pore formers on the surface are more distributed than those inside during mixing and pressing. During the subsequent elimination treatment, the surface pores are more distributed and it is easier to eliminate the pore formers inside, that is, the elimination effect is improved to a certain extent. Therefore, the hydrogen-producing particles prepared in Example 5 also have a certain improvement in the subsequent catalytic hydrogen production effect and hydrogen storage effect compared with Example 4.

[0062] Embodiment 6:

[0063] On the basis of Example 4, the particles were washed and dried with ethanol, aminopropyltriethoxysilane (APTES) was selected as a modifier, and the particles were subjected to modification treatment by reacting at room temperature for 1 hour, and then washed and dried.

[0064] Example 7: Based on Example 6, the metal organic framework material ZIF-8MOF is filled into the porous structure of the hydrogen production particles. The specific filling steps are as follows: Preparation of MOF precursor: Dissolve zinc acetate in DMSO, the mass ratio of zinc acetate to DMSO is 0.8:10, slowly add 2-methylimidazole, and continue stirring until it is completely dissolved, the mass ratio of 2-methylimidazole to DMSO is 1.2:10; immerse the hydrogen production particles in the above solution and keep it standing for 24 hours to ensure that the precursor fully penetrates the particles; place the impregnated particles in The particles were placed in an oven preheated to 100°C for 3 hours to promote the crystallization of ZIF-8. The treated particles were taken out of the oven, cooled naturally to room temperature, rinsed with pure DMSO to remove unreacted precursors and impurities, and then dried at 70°C for 2 hours. The filled metal organic framework material ZIF-8MOF not only has an extremely high specific surface area and stable chemical properties, which can improve the hydrogen adsorption capacity, but also has active sites that can form a strong interaction with hydrogen molecules, thereby increasing the adsorption amount of hydrogen at a lower pressure.

[0065] Embodiment 8:

[0066] The particles prepared in Example 1 were used as catalysts to carry out the hydrogenolysis reaction of cyclohexanone. The reaction mixture was placed in a reactor containing the catalyst, heated to 120°C, and carried out under a pressure of 8 atm. Under these conditions, cyclohexanone was effectively converted into cyclohexanol, demonstrating the potential of porous structured hydrogen production particles in improving the efficiency of hydrogenolysis reactions.

[0067] Embodiment 9:

[0068] The particles prepared in Example 4 were used as catalysts to carry out hydrogenolysis of cyclohexanone. The reaction mixture was placed in a reactor containing the catalyst, heated to 120° C., and carried out under a pressure of 8 atm. Compared with Example 8, it can be found that the efficiency of the hydrogenolysis reaction is significantly improved.

[0069] Embodiment 10:

[0070] The porous hydrogen-producing particles prepared in Example 1 were used as catalyst carriers to carry out hydrogenolysis of ethanol (alcohols). The reactor containing the porous hydrogen-producing particles was heated to 100°C and the reaction was carried out under a pressure of 5 atm. During the reaction, ethanol was effectively hydrogenolyzed under the catalytic action of the particles to generate hydrogen and acetaldehyde.

[0071] Embodiment 11:

[0072] The porous structure hydrogen-producing particles prepared in Example 4 were used as catalyst carriers to carry out the hydrogenolysis reaction of ethanol (alcohols). The reactor containing the porous structure hydrogen-producing particles was heated to 100°C and reacted under a pressure of 5 atm. During the reaction, ethanol was effectively hydrogenolyzed under the catalytic action of the particles to generate hydrogen and acetaldehyde, and the rate of the hydrogenolysis reaction was significantly improved compared to Example 10.

[0073] Embodiment 12:

[0074] The porous structure hydrogen-producing particles prepared in Example 6 were used as catalyst carriers to carry out the hydrogenolysis reaction of ethanol (alcohols). The reactor containing the porous structure hydrogen-producing particles was heated to 100°C and reacted under a pressure of 5 atm. During the reaction, ethanol was effectively hydrogenolyzed under the catalytic action of the particles to generate hydrogen and acetaldehyde, and the rate of the hydrogenolysis reaction was improved to a certain extent compared with Example 11.

[0075] Embodiment 13:

[0076] The porous structure hydrogen-producing particles prepared in Example 7 were used as catalyst carriers to carry out the hydrogenolysis reaction of ethanol (alcohols). The reactor containing the porous structure hydrogen-producing particles was heated to 100°C and reacted under a pressure of 5 atm. During the reaction, ethanol was effectively hydrogenolyzed under the catalytic action of the particles to generate hydrogen and acetaldehyde, and the rate of the hydrogenolysis reaction was improved to a certain extent compared with Example 12.

[0077] Embodiment 14:

[0078] In this example, the particles prepared in Example 1 were tested in a hydrogen storage system. The test was conducted at room temperature and the initial system pressure was set to 1 atm. The particles showed good hydrogen adsorption capacity, and a significant increase in adsorption efficiency was observed by increasing the system pressure to 10 atm. When releasing hydrogen, the particles were able to quickly release the adsorbed hydrogen by reducing the system pressure and appropriately heating to 50°C.

[0079] Embodiment 15:

[0080] In this example, the particles prepared in Example 4 were tested in a hydrogen storage system. The test was carried out at room temperature, and the initial pressure of the system was set to 1 atm. The particles showed good hydrogen adsorption capacity, and by increasing the system pressure to 10 atm, a significant improvement in adsorption efficiency was observed. When releasing hydrogen, by reducing the system pressure and appropriately heating to 50°C, the particles were able to quickly release the adsorbed hydrogen. It can be found that both the hydrogen adsorption efficiency and the hydrogen release efficiency were improved compared to Example 14.

[0081] Embodiment 16:

[0082] In this example, the particles prepared in Example 4 were tested in a hydrogen storage system. The test was carried out at room temperature, and the initial pressure of the system was set to 1 atm. The particles showed good hydrogen adsorption capacity, and by increasing the system pressure to 10 atm, a significant improvement in adsorption efficiency was observed. When releasing hydrogen, by reducing the system pressure and appropriately heating to 50°C, the particles were able to quickly release the adsorbed hydrogen, and it can be found that both the hydrogen adsorption efficiency and the hydrogen release efficiency were improved compared to Example 15.

[0083] Embodiment 17:

[0084] In this example, the particles prepared in Example 4 were tested in a hydrogen storage system. The test was carried out at room temperature, and the initial pressure of the system was set to 1 atm. The particles showed good hydrogen adsorption capacity, and by increasing the system pressure to 10 atm, a significant improvement in adsorption efficiency was observed. When releasing hydrogen, by reducing the system pressure and appropriately heating to 50°C, the particles were able to quickly release the adsorbed hydrogen, and it can be found that both the hydrogen adsorption efficiency and the hydrogen release efficiency were improved compared to Example 16.

[0085] Figure 2-4 Conversion rate refers to the percentage of raw materials converted into products in the hydrogenolysis reaction.

[0086] Product yield: refers to the efficiency of generating the target product.

[0087] Adsorption efficiency: refers to the percentage of hydrogen that the particles can adsorb at a given pressure.

[0088] Release efficiency: refers to the percentage of hydrogen that can be released by the particles under reduced pressure and heating conditions.

[0089] Porosity: refers to the percentage of pore space in a particle to the total volume.

[0090] Hydrogen adsorption capacity: refers to the weight percentage of hydrogen that the particles can adsorb.

[0091] Hydrogen release rate: refers to the rate at which the particles release hydrogen, measured in weight percent per minute.

[0092] In summary, the present invention improves the efficiency and stability of hydrogen storage and hydrogen release through a combination of specific metal hydrides and structural stabilizers. Through specific preparation methods, such as ball milling and thermal annealing processes, the uniformity and structural integrity of the particles are ensured, and at the same time, a special pore former is introduced for preparation, which further significantly improves the porosity of the hydrogen-producing particles, and enhances their hydrogen production catalysis and hydrogen storage performance. In addition, these particles have broad application prospects as catalyst carriers in chemical reactions or in hydrogen storage systems, especially in improving the efficiency of organic compound hydrogenolysis reactions and controlling the adsorption and release of hydrogen in hydrogen storage systems. Unique performance is shown.

[0093] The above are only preferred specific implementations of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and improved concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A porous hydrogen-producing particle, characterized in that: The particles are composed of metal hydride and a structural stabilizer, wherein the metal hydride is selected from at least one of magnesium hydride (MgH2), nickel hydride (NiH2) and iron hydride (FeH2), and the structural stabilizer is carbon nanotubes or metal oxides.

2. The porous hydrogen-producing particle according to claim 1, characterized in that: The mass ratio of the metal hydride is 50-90%, and the mass ratio of the structural stabilizer is 10-50%.

3. The porous hydrogen-producing particle according to claim 1, characterized in that: A pore former is also included, the pore former accounting for 1-5% of the mass of the particle.

4. The method for preparing hydrogen-producing particles with a porous structure according to claim 3, characterized in that: The following steps are involved: a. Mixing metal hydride and structural stabilizer in a certain proportion; b. The mixture is subjected to ball milling at room temperature to form a uniformly mixed powder; c. Pressing the ball-milled powder into particles and curing them by natural curing or thermal annealing, wherein the heating temperature of the thermal annealing is not higher than 200°C.

5. The method for preparing hydrogen-producing particles with a porous structure according to claim 4, characterized in that: In step c, after the particles are solidified, the surfaces are chemically modified to introduce amino or carboxyl functional groups, thereby providing additional adsorption sites or improving the interaction between the particles and hydrogen, including the following processing steps: C1. Clean the particles in an ultrasonic cleaner using a solvent such as ethanol or acetone, and then dry them in an oven; C2. For the introduction of amino functional groups, aminopropyltriethoxysilane (APTES) can be selected as a modifier, and for the introduction of carboxyl functional groups, carboxypropyltriethoxysilane (CPTES) can be selected as a modifier; C3, soaking the prepared particles in a solution containing a modifier and reacting at room temperature for 1-2 hours; C4, recovering the modified particles from the reaction mixture and washing them thoroughly with ethanol to remove unreacted modifiers and byproducts; C5. Finally, the cleaned particles are dried at 30-40°C for 1-5 hours to ensure that the modifier is solidified and stably attached to the particle surface.

6. The method for preparing hydrogen-producing particles with a porous structure according to claim 4, characterized in that: The specific steps of adding the pore former are as follows: S1. Prepare a pore former of corresponding mass, and evenly mix 80-90% of the mixed powder and 60-80% of the pore former after step b; S2, pressing and molding the mixed product of step S1 to form initial particles, and uniformly mixing the remaining mixed powder with the pore-forming agent to wrap the initial particles for secondary pressing and molding to form final particles; S3. The final particles are treated to eliminate the pores left by the pore former to form hydrogen-producing particles.

7. The method for preparing hydrogen-producing particles with a porous structure according to claim 6, characterized in that: After step S3, the metal organic framework material ZIF-8MOF is filled into the porous structure of the hydrogen production particles. The specific filling steps are as follows: S4. Preparation of MOF precursor: Dissolve zinc acetate in DMSO, the mass ratio of zinc acetate to DMSO is (0.8-1):10, slowly add 2-methylimidazole, and continue stirring until completely dissolved, the mass ratio of 2-methylimidazole to DMSO is (1-1.2):10; S5. Impregnation: Immerse the hydrogen-producing particles in the above solution and keep them still for 12 to 24 hours to ensure that the precursor fully penetrates the interior of the particles; S6. Low temperature heat treatment: placing the impregnated particles in an oven preheated to 100°C for 2-3 hours to promote ZIF-8 crystallization; S7, cooling and recycling: taking out the treated particles from the oven, cooling them naturally to room temperature, washing the particles with pure DMSO to remove unreacted precursors and impurities, and then drying them at 60-80°C for 1-2 hours.

8. The method for preparing hydrogen-producing particles with a porous structure according to claim 4, characterized in that: The pore former is one of gelatin and carboxymethyl cellulose, and step S3 is eliminated by a corresponding low-temperature treatment method.

9. The use of a porous hydrogen-producing particle according to any one of claims 1 to 3, characterized in that: The particles are used as catalyst supports for catalyzing hydrogenolysis of organic compounds.

10. The use of the porous hydrogen-producing particles according to claim 9, characterized in that: The particles are also used in hydrogen storage systems, where the porous structure increases the efficiency of hydrogen adsorption and release.